Knowledge Sharing Pelayan Anak di Pelkat Pelayanan Anak GPIB Gloria - Elisa Christiana Sulardja; Elnovani Lusiana; Asep Saeful Rohman (Sekolah Tinggi Teologi Nusantara, 2021)
This study aims to determine knowledge sharing of child servants in Pelkat PA GPIB Gloria Bekasi. The research method used is qualitative with case study approach. Data collection techniques were used through observation, interviews, documentation, and literature study. This research was conducted on 4 informants who were members of Pelkat PA GPIB Gloria. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The study was conducted around 10 months. The results are: 1) knowledge sharing’s process: socialization, externalization, combination, and internalization, 2) behavior knowledge sharing: subject norms, attitude, perceived behavioral control, and social network ties, and 3) constraints knowledge sharing: lack of time, benefits to oneself and other, fear and uncertainty, and technological context. This research is to understand knowledge sharing contribution by child servants at Pelkat PA GPIB Gloria.